Sistem Informasi Aplikasi Akademik (Si-Apik) Berbasis Android - saifudin; Paiman Paiman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2022)
Al-Qur'an Education Park (TPQ) is an institution or community group that organizes non-formal education in the type of Islamic religion that aims to provide reading of the Qur'an from an early age, and discusses the basics of the Islamic tradition in ancient times. kindergarten, elementary school and / or madrasah ibtidaiyah (SD / MI) or even higher. In the era of globalization it is hoped that scientific development can be followed. At the TPQ Al-Falah Foundation, Bobosan Purwokerto specifically on the TPQ unit, the process of increasing volumes, and the development of students during learning, is still done manually, making academic systems to improve volumes used, repairing compilation improvements, and asking students to be tested to testers because they have to save data of students requested and must meet with examiners directly. By using android technology as a component to create SI APIK Application, it is expected to be able to provide clerics / clerics in the academic process of increasing volumes so that they no longer use paper as a storage and delivery medium. The results of this study are the clerics / clerics can easily carry out the process of increasing volumes. It is expected that future application research can be developed with a broader academic scope.